Description of a new species of Liaghinella (Hemiptera: Heteroptera: Reduviidae: Emesinae) from the Colombian Andes, with notes on its feeding habits and conservation status - Forero, Dimitri (Zootaxa, 2007)
Liaghinella andina sp. nov. is described from the eastern Colombian Andes. Until now, the genus Liaghinella Wygodzinsky, 1966 included only L. farri Wygodzinsky, 1966, described from Jamaica. To find this new species for the first time in continental South America and at so high an altitude is remarkable. The new species is close to L. farri, but differs in color pattern, and in the structure of the head, male genitalia, and fore leg armature. For the first time a female of Liaghinella is described and sexual differences are highlighted. Keys to separate the related genera and the two known species of Liaghinella are provided. Biological information on the new species’ feeding habits on spiders is presented and discussed. Dorsal habitus photographs, in addition to photographs and illustrations of other morphological structures, are provided. Finding this new species in the remnants of an Andean montane forest adjacent to urban areas highlights the necessity of local conservation efforts in the Colombian Andes.Se describe Liaghinella andina sp. nov. de la cordillera oriental de los Andes colombianos. El género Liaghinella incluía únicamente a L. farri Wygodzinsky, 1966, descrita de Jamaica. Por primera vez se registra este género en Sudamérica continental y a gran altitud. La nueva especie es muy similar a L. farri, pero difiere de aquella por el patrón de coloración, la estructura de la cabeza, la genitalia masculina y la serie anteroventral de las patas anteriores. Por primera vez se describe una hembra de Liaghinella resaltándose las diferencias entre sexos. Se proporciona una clave para separar las dos especies conocidas, y otra para los géneros relacionados. Se brinda y discute la alimentación con arañas. Se presentan fotografías de los habitus dorsales, así como fotografías e ilustraciones de otros detalles estructurales. El haber encontrado esta nueva especie en remanentes de bosques Andinos muy cercanos a centros urbanos resalta la necesidad de esfuerzos de conservación locales.